DAMPAK MANAJEMEN UTANG USAHA PADA KINERJA PERUSAHAAN: STUDI EMPIRIS DI BURSA EFEK INDONESIA - Lucia Iswandari (PROSIDING, 2022)
Accounts payable management is part of the task that must be considered by company managers. This study aims to examine the effect of accounts payable management on the financial performance of companies listed on the Indonesia Stock Exchange. The number of observations is 189 observations. The test is carried out by applying regression analysis to the data panel by applying the fixed effect and random effects models. The test results found findings that did not support the existence of a quadratic effect of the use of accounts payable on the company's financial performance. Several suggestions were put forward to improve the quality of this article in the future. Keywords: accounts payable management, financial performance.